KALAH ATAU MENGALAH: INTERAKSI DOMINASI DALAM PERKAWINAN ADAT SUKU BUGIS - M. Amir Mahmud (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
This study delves into the dynamics of interaction between families in Bugis traditional marriages, with a specific focus on the significance of "uang panai’" (bride price). While existing research explores the meaning of "uang panai’", there is a notable gap in understanding the interaction dynamics between families, crucial for Bugis traditional weddings. The study emphasizes the groom's perception of "uang panai’" as a mandatory requirement and argues that this understanding influences marriage sustainability. Methodologically, a library research approach is employed. The findings reveal that "uang panai’" extends beyond a mere condition for marriage, symbolizing social status for Bugis brides. The study contributes insights into power dynamics and gender roles within Bugis marriage customs.